Psychosocial Adjustment and Mental Distress Associated With In-Game Purchases Among Japanese Junior High School Students - Shinkawa, Hiroki; Irie, Tomonari; Tanaka, Masanori; Yokomitsu, Kengo (Frontiers in Psychology, 2021)
In-game purchases, also known as microtransactions and loot box spending, are the monetization systems of free-to-play online games. Although some studies have suggested that excessive in-game purchases increase the risk of psychosocial maladjustment and mental distress as well as predict future problematic gaming and gambling practices, empirical studies into the behavior of adolescents who make such in-game purchases are lacking. This study sought to clarify whether psychosocial adjustment and mental distress status could be compared with the purchase style (non-purchase, planned purchase, and unplanned purchase) of adolescents in order to characterize problematic in-game purchasers. A total of 335 junior high school students (aged 12–15 years) participated in the survey and completed a questionnaire assessing daily online gaming usage, in-game purchases, psychosocial adjustment, and mental distress. The results showed that (1) 30.7% of students had previously made in-game purchases, and at least 14.0% had made unplanned in-game purchases; (2) close to a quarter of the users who had made unplanned purchases had spent much more than their average monthly allowance within the past month, and (3) unplanned purchase gamers exhibited significant behavioral conduct problems and peer problems regarding psychosocial adjustment compared to planned purchase gamers. These findings support the theory that whether adolescents have a planned intention to engage in the process of in-game purchasing is an important predictor of the risk of psychosocial maladjustment linked with problematic online gaming.